Effects of Pereskia aculeate Miller Petroleum Ether Extract on Complete Freund’s Adjuvant-Induced Rheumatoid Arthritis in Rats and its Potential Molecular Mechanisms - Chen, Yifei; Liu, Kaifei; Qin, Yingyuan; Chen, Suyi; Guan, Guokai; Huang, Yao; Chen, Yu; Mo, Zhixian (Frontiers in Pharmacology, 2022)
Objective: To investigate the therapeutic effect of petroleum ether extract of Pereskia aculeate Miller (PEEP) on rheumatoid arthritis (RA). Methods: In vitro: The Cell Counting Kit-8 (CCK-8) was used to detect cell activity and select the optimal concentration of the extract; the effective site was screened by nitric oxide (NO) colorimetric method and Q-PCR method; the expression of p38, p-p38, p-MK2 and Tristetraprolin (TTP) in RAW 264.7 cells were detected by Western blot. In vivo: The rat model was established by complete Freund's adjuvant (CFA). The different doses of PEEP on CFA rats were observed with life status, paw swelling, spleen index, X-ray, HE staining; the secretion of Tumor necrosis factor α (TNF-α), interleukin-6 (IL-6) and Prostaglandin E2 (PGE2) were detected by Enzyme linked immunosorbent assay (ELISA); the expressions of p38, p-p38, p-MK2 and TTP in the ankle joints of CFA rats were detected by Western blot. Result: In vitro: PEEP, Ethyl Acetate Extract of Pereskia aculeate Miller (EEEP), N-butanol Extract of Pereskia aculeate Miller (BEEP) have no toxic effects on RAW264.7 macrophages. PEEP, EEEP and BEEP reduce the secretion of NO in RAW264.7 cells induced by lipopolysaccharide (LPS), only PEEP significantly inhibited the mRNA expression levels of inflammatory factors TNF-α and IL-6; PEEP-dependently reduce the secretion of TNF-α and IL-6, decrease the expression of p-p38 and p-MK2, and the level of TTP phosphorylation in LPS-induced RAW264.7 cells. In vivo: PEEP improve the living conditions of CFA rats, reduce foot swelling, spleen index, bone surface erosion and joint space narrowing; reduce the formation of synovial cells, inflammatory cells and pannus in the foot and ankle joints. PEEP reduce the secretion of TNF-α, IL-6, PGE2 in rat serum, down-regulate the expression of p-p38 and p-MK2 in the ankle joint, and reduce the phosphorylation of TTP. Conclusions: PEEP improve the living conditions of CFA rats, reduce the degree of foot swelling, protect immune organs, reduce inflammatory cell infiltration, cartilage damage, pannus formation, reduce inflammation and RA damage. The mechanism through regulating the signal pathway of p38 mitogen-activated protein kinase (p38/MAPK), which reduces the release of TNF-α, IL-6, and PGE2 in the serum.